Explicación funcional y sociología popular. Functional explanation and folk sociology - César Rendueles (Logos, 2006)
This essay analyzes the functional explanation’s defence that G. A. Cohen advanced on the occasion of his updating of the main thesis of the historical materialism theory and suggests and alternative. Cohen put forward a law-like version of the functional explanation based on the dispositional features of some typical social science’s statements. This essay, on the contrary, advances a way for interpreting functional explanations as identity assertions in the extensionally vague –but no immediately intensional– contexts typical both of naive daily explanations and folk sociology.